Conditions for Effective Long-Term Energy Supply to the Arctic Areas of the Republic of Sakha (Yakutia) - Elyakova, Izabella D.; Elyakov, Aleksandr L.; Karataeva, Tamara A.; Khristoforov, Aleksandr A.; Buryanina, Nadezhda S.; Fedorov, Afanasiy A. (International Journal of Energy Economics and Policy, 2018)
This paper presents a comparative assessment of the efficiency of electricity production and consumption in the Eastern Economic Zone (EEZ) of the Republic of Sakha (Yakutia). Based on the analysis, the existing electricity supply risks in the EEZ areas are identified and recommendations for efficient electricity consumption and production in the EEZ areas are developed. The study makes it possible to develop sound recommendations for improving the efficiency of electricity production and consumption in the Oymyakonsky District of the EEZ. No relevant studies of the Eastern Economic Zone, including the Oymyakonsky District in the Republic of Sakha (Yakutia), have been conducted over the past five years. In this regard, the relevance of the study stems from the fact that not only natural but also cost indices of electricity production and consumption are calculated for the first time, and recommendations for efficient electricity consumption are given in the context of the Oymyakonsky District settlements of the EEZ. Keywords: Electric Power, Electricity Generation and Consumption, Eastern Economic Zone. JEL Classifications: Q4, R0, R1 DOI: https://doi.org/10.32479/ijeep.7031